(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Space (Yin-Yang Infinity????), the universe (Yin-Yang Taiji????), all things in the world, humanity, and existence (Yin-Yang Heaven-Earth????) are objective realities independent of human subjective consciousness. The universe created matter and humanity; humans are a form of matter. Humans created languages, scripts, numbers, mathematics, coordinate systems, and science, along with philosophy and religion, thereby forming the human system of knowledge and information. The correctness of human-created knowledge and information must be verified through scientific reproducibility and probability. Humans created knowledge and information to explore cosmic truth for survival and existence. However, human-made existence never equates to ultimate truth but perpetually approaches it. Material philosophy and material science allowed humans to understand human society and the three-dimensional material world. Quantum mechanics and the theory of relativity opened the doors to energy philosophy and information philosophy, ushering humanity into cosmic origin philosophy. This complemented human knowledge and information, further expanding the pathways for humanity’s contemplation of cosmic truths.